2010
DOI: 10.1017/s1751731109991479
|View full text |Cite
|
Sign up to set email alerts
|

Effects of duration of zilpaterol hydrochloride supplementation on growth performance, carcass traits and meat quality of grain-fed cull cows

Abstract: Several studies have shown that feeding of an energy-dense diet over short periods to cull cows could be profitable in terms of increased saleable yield and improved carcass conditions. Although the application of growth promoters, such as anabolic implants and beta agonists, in finishing of cull cows have been recorded, there is no conclusive evidence as to the timing and duration of beta agonists in cull cow production. In this study, 288 cull cows with four or more permanent incisors and varying weights and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
4
4
0
Order By: Relevance
“…These results agree with effects of ZH on fat deposition of finishing ewe lambs under heat stress (Macias-Cruz et al, 2010). In general, several studies in the literature in which effects of ZH were evaluated on deposition of internal fat in heifers and culled cows agree with the results of the present study Neill et al, 2009;Robles-Estrada et al, 2009a;Strydom and Smith, 2010). Zilpaterol is considered a repartitioning agent that primarily functions through an increase of protein deposition, whereas other composition factors such as moisture, fat, and ash seem to be minimally affected (Leheskaet al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…These results agree with effects of ZH on fat deposition of finishing ewe lambs under heat stress (Macias-Cruz et al, 2010). In general, several studies in the literature in which effects of ZH were evaluated on deposition of internal fat in heifers and culled cows agree with the results of the present study Neill et al, 2009;Robles-Estrada et al, 2009a;Strydom and Smith, 2010). Zilpaterol is considered a repartitioning agent that primarily functions through an increase of protein deposition, whereas other composition factors such as moisture, fat, and ash seem to be minimally affected (Leheskaet al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…After 10 d and 21 d of aging, LM steaks from ZH and RH+ZH treatments had a lower (Pb 0.0001) percentage of degraded desmin than steaks from C cows or cows supplemented only with RH. As expected, for all treatments, a higher percentage of degraded desmin was present after 21 d of postmortem aging than at 10 d. In contrast to our results, Kellermeier et al (2009) reported that ZH supplementation in steers did not alter desmin degradation in LM steaks aged for 7, 14, and 21 d. In support of our results, Strydom and Smith (2010) reported increased calpastatin activity in steaks from β-AA-supplemented steers. We speculate that desmin degradation was lower in ZH-fed cattle because of increased muscle calpastatin activity, and, thereby, reduced postmortem proteolysis.…”
Section: Non-enhanced Longissimus Warner Bratzler Shear Force and Sensupporting
confidence: 87%
“…In young cattle, β-AA have profound effects on growth performance and carcass yields, but several studies have shown that the effectiveness of β-AA in mature cows is less pronounced (Carter, Johnson, Thrift, & Foster, 2006;Harborth, 2006;Holmer, Homm, Berger, McKeith, & Killefer, 2009;Neill et al, 2009). In contrast, Strydom and Smith (2010) and Lawrence, Gasch, Hutcheson, and Hodgen (2011) reported increased performance, carcass yield, and conformation scores when cows were supplemented with ZH at 8.33 mg head −1 for 30 d.…”
Section: Introductionmentioning
confidence: 99%
“…There is divergence in the reported effects of zilpaterol on DMI, with reports ranging from small to moderate decreases in DMI (Baxa et al, 2010;Holland et al, 2010;Parr et al, 2011) to reports of greater decreases (Scramlin et al, 2010;McKevers et al, 2012a). South African researchers have reported reduced DMI of 6% in steers (Strydom et al, 2008) and 5% in cull cows (Strydom and Smith, 2010) fed ZIL at 6 mg/kg, although these reductions were not statistically significant. Vasconcelos 2008) demonstrated a 0.40 kg reduction in DMI when ZIL was fed for 40 d at 72 mg/animal daily but no effect on DMI for cattle fed ZIL at 75 mg/animal daily for 20 d. Montgomery et al (2009a) reported a ZIL × sex interaction for DMI; steers did not have a reduction in DMI during ZIL administration but heifers had a 0.52 kg reduction in DMI during the ZIL-feeding period.…”
Section: Figurementioning
confidence: 94%